Centros de Educação Ambiental como possíveis espaços de fortalecimento da educação integral - Jardim, Tania Perfeito (2024)
This study sought to investigate the potential of Environmental Education Centers (CEA) as a component of curricular proposals. The dissertation presents CEAs as educational equipment to support formal education in the construction of a curriculum connected with the territory and committed to socio-environmental issues at a local and global level, thus strongly collaborating with the search for an integral education. The research analyzed the approaches between critical environmental education, the democratic curriculum and curricular justice, in order to highlight that these elements, when merged into a political pedagogical project (PPP) of a CEA, contribute to the achievement of emancipatory education. The study path also covers historical environmental landmarks worldwide, presenting how these influences Brazilian environmental education policy and how this is present in the guiding documents of national education. When analyzing the CEA of Sesc Guarulhos and its relationship with CONAMA Recommendation nº 11, of May 4, 2011, it highlights the complementarities between non-formal education and formal education to achieve a comprehensive education. Regarding the methodology, we opted for an exploratory, descriptive study with a qualitative bias, carried out through bibliographical, documentary and field research, based on a case study. The field research was carried out through semi-structured interviews, direct observation of the facilities and analysis of the educational proposal of the CEA of Sesc Guarulhos. In this dissertation, the approach to CEA and critical environmental education was supported by Sorrentino (2000), Sorrentino et al (2005, 2007), Sorrentino and Portugal (2016), Marques et al (2019), Layrargues (2014), Loureiro (2007, 2012, 2018), Silva (2002, 2005); Silva and Sorrentino (2002, 2005). Comprehensive education was authored by Moll (2012) and Moll and Dutra (2018). Arroyo (2012, 2013) and Adorno (1996) were consulted on the proposal for an emancipatory and democratic curriculum. To reflect on curriculum and, specifically, on curricular justice, Torres Santomé (2013, 2017), Ponce (2016) and Ponce and Araujo (2018, 2019, 2021). From an emancipatory perspective, the investigation recognized that CEA can contribute to the critical school curriculum from the perspective of integral education, as they collaborate with educational elements that encourage the reading of the world based on socio-environmental phenomena, sensitizing students to the exercise of citizenship